Superresolution architecture of cornerstone focal adhesions in human pluripotent stem cells - Aki Stubb; Camilo Guzmán; Elisa Närvä; Jesse Aaron; Teng-Leong Chew; Markku Saari; Mitro Miihkinen; Guillaume Jacquemet; Johanna Ivaska (Nature Publishing Group, 2022)
While it is clear that key transcriptional programmes are important for maintaining pluripotency, the requirement for cell adhesion to the extracellular matrix remains poorly defined. Human pluripotent stem cells (hPSCs) form colonies encircled by an actin ring and large stable cornerstone focal adhesions (FA). Using superresolution two-colour interferometric photo-activated localisation microscopy, we examine the three-dimensional architecture of cornerstone adhesions and report vertical lamination of FA proteins with three main structural features distinct from previously studied focal adhesions: 1) integrin β5 and talin are present at high density, at the edges of cornerstone FA, adjacent to a vertical kank-rich protein wall, 2) vinculin localises higher than previously reported, displaying a head-above-tail orientation, and 3) surprisingly, actin and α-actinin are present in two discrete z-layers. Finally, we report that depletion of kanks diminishes FA patterning, and actin organisation within the colony, indicating a role for kanks in hPSC colony architecture.